Distribution and Prevalence of Various Developmental Dental Anomalies in Iraqi population : A Radiographic Study (Mustansiria Dental Journal, 2019)
Aim: To determine the prevalence of dental anomalies in Iraqi population, andinvestigate their possible association with gender and teeth.Materials and methods: Panoramic radiographs of 800 patients out of 350 withdental anomalies (200 females and 150 males) ,an age range of 18–30 years ( 300: 18-25 years ; 50: 25-30 years ) were examined for anomalies in teeth number,shape, size and position.Descriptive statistics was performed using SPSS. Thelevel of significance was set at 95% confidence level.Results: Among the 800 radiographs examined, a total of 350 (43.8 %) haddevelopmental dental anomalies which includes 150 (42.9%) males and 200(57.1%) females. Around 290 (82.9%) had at least one anomaly, 50 (14.2%) caseswith two anomalies and only 10 (2.9%) exhibited more than two anomalies. Bothmales and females were equally affected. Of these 350 anomalies, 300 (85.7%)occurred in the age group 18–25 years compared to 50 (14.3%) cases in 25–30years range .Conclusion: The high prevalence of Developmental Dental Anomalies suggests theneed to increase the understandingof their etiology and aid for better management,intervention and prevention.